Antiviral Resistance and Phage Counter Adaptation to Antibiotic-Resistant Extraintestinal Pathogenic Escherichia coli - Salazar, Keiko C. (mBio, 2021)
Extraintestinal pathogenic Escherichia coli (ExPEC), often multidrug resistant (MDR), is a leading cause of urinary tract and systemic infections. The crisis of emergent MDR pathogens has led some to propose bacteriophages as a therapeutic. However, bacterial resistance to phage is a concerning issue that threatens to undermine phage therapy. Here, we demonstrate that E. coli sequence type 131, a circulating pandemic strain of ExPEC, rapidly develops resistance to a well-studied and therapeutically active phage (ϕHP3). Whole-genome sequencing of the resisters revealed truncations in genes involved in lipopolysaccharide (LPS) biosynthesis, the outer membrane transporter ompA, or both, implicating them as phage receptors. We found ExPEC resistance to phage is associated with a loss of fitness in host microenvironments and attenuation in a murine model of systemic infection. Furthermore, we constructed a novel phage-bacterium bioreactor to generate an evolved phage isolate with restored infectivity to all LPS-truncated ExPEC resisters. This study suggests that although the resistance of pandemic E. coli to phage is frequent, it is associated with attenuation of virulence and susceptibility to new phage variants that arise by directed evolution.